Sharing Knowledge and Build a Better Mindset di SMK Widya Nusantara - Prastio, Eko; Marsiyanto, Nugroho; Susanto, Edy (Jurnal Sains Teknologi dalam Pemberdayaan Masyarakat, 2024)
Knowledge sharing aims to spread knowledge or information. Usually this can be in the form of activities, discussions, presentations, tutors, and many others. With the right implementation, knowledge sharing can be done well so that everyone can feel the benefits, develop and learn from each other. Knowledge sharing that can be done in increasing the potential and competence of students, can use various other ways, one of which is by making students more obedient in terms of rules at school. Having broad insight is very important for all of us. Therefore, this millennial generation must have broad insight and think better. Students as one of the components in this matter, are required to be the party that bridges the gap. In other words, the real thing that must be done by students is to help students to be able to develop for the better. Students become the driving force of change in this country who will hold the leadership relay in the future, therefore students must play an active role in being the pioneers of forming a sense of leadership. For this reason, knowledge and abilities are needed. Besides that, the development of abilities in students is very important so that they can give birth to a good next generation.